MHD Flow past a Semi-Infinite Vertical Plate with Mass Transfer - Palani, G.; Srikanth, U. (Nonlinear Analysis: Modelling and Control, 2009)
An analysis is performed to study the MHD flow of an electrically conducting, incompressible, viscous fluid past a semi-infinite vertical plate with mass transfer, under the action of transversely applied magnetic field is carried out. The heat due to viscous dissipation and the induced magnetic field are assumed to be negligible. The dimensionless governing equations are unsteady, two-dimensional, coupled and non-linear partial differential equations. A most accurate, unconditionally stable and fast converging implicit finite difference scheme is used to solve the non-dimensional governing equations. The effects of external cooling (Gr > 0) of the plate by the free convection are studied.